Aplikasi Absensi Online Berbasis Web Menggunakan Algoritma Sequential Searching - Arif Febrianto; Fauziah F; Iskandar Fitri (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
Attendance application is very important to know the presence of its employees in a company. The finger print method is very inconvenient for attendance managers, especially when recapitulating attendance data, plus the Aroma Kopi company currently has implemented WFH so that it requires sufficient time for attendance with the finger print method. Employees are required to make a work report by submitting proof of work and attendance. From the large number of employee data, it will be very difficult for data managers to find attendance data and employee data. The purpose of this study is to test the attendance application as a tool for employee attendance during the current WFH period, and can help data managers in searching data, so data can be found more quickly. And make it easier for system managers to report employee attendance which will later be submitted to superiors. Sequential Searching Algorithm is a method used to find data more quickly and effectively. In the test results of each tested function is valid, and it can be concluded that the Search method can run well and as expected. The speed performance of the sequential searching method with 10 employee data and 60 attendance data reached an average of 0.02 seconds.